2020
DOI: 10.22424/jdsb.2020.38.4.207
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characteristics and Anti-Obesity Effect of Milk Fermented by Lactobacillus plantarum KI134

Abstract: This study aimed to investigate the physiological characteristics and anti-obesity effects of milk fermented by L. plantarum KI134. The lipase, α-amylase, and α-glucosidase inhibitory activities of milk fermented by L. plantarum KI134 was 94.57±1.25%, 9.44±2.85%, and 2.74±1.24% (10 fold dilution), respectively. L. plantarum KI134 showed higher sensitivity to clindamycin and erythromycin in comparison to sixteen different antibiotics. It demonstrated the highest resistance toward ampicillin and vancomycin. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…The degree of adipocyte differentiation inhibition was dependent on the concentration of CFE treatment and was enhanced by MG4244 compared to MG4231. Kim et al (2018) reported that L. plantarum K10 treatment (100 lg/mL) inhibited adipocyte differentiation of 3T3-L1 cells by 32%. Exopolysaccharide (EPS) is a component of the lactic acid bacteria (LAB) cell envelope or is a primary or secondary metabolite that accumulates in a viscous form outside the cell wall during fermentation.…”
Section: Effects Of L Fermentum Mg4231 and Mg4244 Strains On Adipocyte Differentiationmentioning
confidence: 99%
“…The degree of adipocyte differentiation inhibition was dependent on the concentration of CFE treatment and was enhanced by MG4244 compared to MG4231. Kim et al (2018) reported that L. plantarum K10 treatment (100 lg/mL) inhibited adipocyte differentiation of 3T3-L1 cells by 32%. Exopolysaccharide (EPS) is a component of the lactic acid bacteria (LAB) cell envelope or is a primary or secondary metabolite that accumulates in a viscous form outside the cell wall during fermentation.…”
Section: Effects Of L Fermentum Mg4231 and Mg4244 Strains On Adipocyte Differentiationmentioning
confidence: 99%
“…On the basis of emerging evidence, the consumption of dietary probiotics is an effective strategy to prevent inflammation and obesity via multiple mechanisms, including fortifying gut barrier function, maintaining the equilibrium of the gut microbiota, and balancing energy homeostasis . One probiotic, Lactobacillus plantarum K10, which is isolated from kimchi, exhibited an anti-obesity property by binding to the mucosa and forming a barrier to protect the gut and regulate intestinal permeability when mice were fed an HFD . According to another study, in mice fed an HFD, supplementation with Lactobacillus curvatus HY7601 and Lactobacillus plantarum KY1032, which are found in traditional Korean fermented cabbage, decreased the overall body weights of the mice.…”
Section: Introductionmentioning
confidence: 99%
“…Yoghurt tends to contribute to faster satiety and is thereby advantageous for those in calorie-restricted diets [6]. The bacterial strain in yoghurt makes it an ideal source of anti-obesity agents, and studies have proven that these bacterial cultures are able to tolerate the acidity in the gut and survive in the intestinal tract [7]. Thus, lipolysis, amelioration of cognitive function, and reduction in the absorption of cholesterol are commonly documented features in those who consume yoghurts [8].…”
Section: Introductionmentioning
confidence: 99%